Composting reflections for development. Issue 1 (2nd January 2016) - Cowan, John; Stroud, Rosalind
Abstract: From an anecdotal rumination, the authors make the case for consideration of past reflections, in what they call 'composting', to inspire and enrich new, different and currently ongoing reflective activity and initiatives.